A recombinant collagen filling material and a preparation method and application thereof

CN122973708APending Publication Date: 2026-10-27XI AN ZHEN YAN SHENG WU KE JI YOU XIAN GONG SI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611326917.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,该类基于DMTMM的直接交联技术,在实际应用中常面临力学支撑性弱、体内抗降解能力不足的问题

Benefits of technology

[0027]1、本发明的重组胶原蛋白填充材料采用重组胶原蛋白絮凝物和重组胶原蛋白经羧基活化剂交联制成,通过调控重组胶原蛋白絮凝物与重组胶原蛋白的复配比例,使制备的填充凝胶呈现剪切稀化特性与优异的触变性恢复能力。其中,本发明制备的填充材料触变性恢复率为92.9%~95.8%,表明材料在注射后能够迅速恢复黏弹状态,有利于在填充部位原位塑形并减少移位风险。剪切稀化倍数为53.89~149.71,表明材料在高剪切条件下黏度显著降低,推注顺畅,便于临床注射操作,可兼顾临床操作便利性与填充效果稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122973708A_ABST
    Figure CN122973708A_ABST
Patent Text Reader

Abstract

The application discloses a kind of recombinant collagen filling materials and preparation method and application thereof.The filling material is made of recombinant collagen flocculate and recombinant collagen by carboxyl activator crosslinking, and the method comprises the following steps: preparing recombinant collagen flocculate by alcohol precipitation and gradient salting of recombinant collagen solution;The recombinant collagen flocculate is added into the carboxyl activator solution together with the recombinant collagen, stirred uniformly, and then placed to obtain gel;After dialysis treatment, filling and sterilization, the recombinant collagen filling material is obtained.The recombinant collagen filling material prepared by the application has good mechanical support, long-term anti-degradation performance and aesthetic compatibility, and can meet the clinical needs of safe and long-acting filling materials in the field of medical cosmetology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of gel filler material technology, specifically relating to a recombinant collagen filler material, its preparation method, and its application. Background Technology

[0002] With socio-economic development and improved living standards, consumers' demand for skin anti-aging is becoming increasingly urgent, driving the rapid development of anti-aging products in the medical aesthetics field. Collagen, as a core functional component of the human extracellular matrix, accounts for 70% to 80% of the dry weight of the dermis. Due to its natural biocompatibility, bioactivity, and mechanical support properties, it has become a core raw material in the field of medical aesthetic filler anti-aging.

[0003] Currently available collagen filler products can be divided into two main categories based on their raw material source: One category consists of extract-based collagen products, represented by the Shuangmei series. These are extracted from natural tissues and retain some of the triple helix structure and mechanical properties of natural collagen. However, they pose risks of immunogenicity and rapid degradation. Furthermore, the chemical cross-linking agents used in their preparation, such as glutaraldehyde and genipin, may trigger chronic inflammatory reactions, raising concerns about their safety. The other category consists of recombinant collagen fillers, represented by the Weiyimei series. These are prepared using genetic engineering technology, which effectively reduces the risk of immunogenicity. However, they still suffer from insufficient mechanical support and short retention time in the body, making it difficult to meet the clinical needs for long-lasting fillers.

[0004] To address the aforementioned technical issues, Chinese invention patent application CN119101256A discloses a cross-linked recombinant collagen gel. This gel activates the carboxyl groups on the side chains of collagen molecules using 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMTMM), which then undergoes acylation reactions with intramolecular / intermolecular amino groups to form peptide bonds, enabling collagen molecules to construct a network structure through side chain cross-linking. However, this type of direct cross-linking technology based on DMTMM often faces problems such as weak mechanical support and insufficient in vivo anti-degradation ability in practical applications. Furthermore, this cross-linked gel is a transparent system; due to the difference in refractive index between the material and skin tissue, it easily exhibits a blue translucent appearance when injected into the superficial dermis due to the Tyndall effect, affecting the naturalness of the filled area.

[0005] Given that existing collagen fillers generally suffer from insufficient mechanical support, rapid degradation in vivo, and poor biocompatibility, there is an urgent need in this field to develop a recombinant collagen filler that combines high mechanical support, long-lasting anti-degradation properties, and excellent aesthetic compatibility to meet the clinical needs of the medical aesthetics field for safe and long-lasting anti-aging products. Summary of the Invention

[0006] This invention aims to overcome the shortcomings of the prior art by providing a recombinant collagen filler material, its preparation method, and its application. The filler material is made by cross-linking recombinant collagen flocculants and recombinant collagen with a carboxyl activator. By controlling the ratio of recombinant collagen flocculants to recombinant collagen, the prepared filler gel can exhibit shear-thinning properties and excellent thixotropic recovery. The filler material exhibits significantly reduced viscosity under high shear conditions, resulting in smooth injection and facilitating clinical injection, thus balancing clinical ease of use with stable filling effects.

[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a recombinant collagen filler material, characterized in that it is made by cross-linking recombinant collagen flocculants and recombinant collagen with a carboxyl activator; the recombinant collagen flocculants are flocculants with a microsphere-fiber composite structure prepared by alcohol precipitation and gradient salting out of recombinant collagen solution.

[0008] The above-mentioned recombinant collagen filler material is characterized in that the preparation method of the recombinant collagen flocculant includes:

[0009] Step 1: Add recombinant collagen to a buffer solution with a pH of 7.2-7.4 to prepare a recombinant collagen solution with a mass fraction of 0.5%-3.0%;

[0010] Step 2: Under stirring conditions, anhydrous ethanol is added dropwise to the recombinant collagen solution described in Step 1. After the addition is complete, stirring is continued to obtain product 1.

[0011] Step 3: Centrifuge, wash, and dry the product 1 obtained in Step 2 to obtain product 2;

[0012] Step 4: Perform gradient salting out on product 2 obtained in step 3. The specific process includes: dispersing product 2 at a mass fraction of 3.0% to 5.0% in a phosphate buffer solution with a total salt concentration of 0.05 mol / L to 0.20 mol / L and a pH of 7.2 to 7.4, and stirring at a rate of 10 r / min to 50 r / min for 1 h to 5 h; then increasing the total salt concentration in the system to 0.30 mol / L to 0.50 mol / L, and stirring at a rate of 100 r / min to 200 r / min for 1 h to 5 h; then increasing the total salt concentration in the system to 0.70 mol / L to 0.90 mol / L, stirring until the salt dissolves, and then allowing it to stand for 8 h to 12 h to obtain product 3.

[0013] Step 5: Filter, wash and dry the product 3 obtained in step 4 to obtain recombinant collagen flocculent.

[0014] The recombinant collagen filler material described above is characterized in that the buffer solution in step one is any one of phosphate buffer solution, 4-hydroxyethylpiperazine ethanesulfonic acid (HEPES) buffer solution, 3-morpholinopropanesulfonic acid (MOPS) buffer solution and piperazine-1,4-diethanesulfonic acid (PIPES) buffer solution;

[0015] The salt used to increase the salt concentration in step four is one or more of the following: ammonium sulfate, sodium sulfate, disodium hydrogen phosphate, potassium dihydrogen phosphate, and sodium chloride.

[0016] The recombinant collagen filler material described above is characterized in that, in step two, the stirring rate is 100 r / min to 300 r / min, the volume ratio of anhydrous ethanol to recombinant collagen solution is 1:(1~3), the dropping rate of anhydrous ethanol is 0.1 mL / min to 0.5 mL / min, and after the dropping is completed, stirring is continued at a rate of 100 r / min to 300 r / min for 1 h to 5 h.

[0017] The recombinant collagen filler material described above is characterized in that the centrifugation rate in step three is 3000 r / min to 5000 r / min, and the centrifugation time is 1 min to 10 min.

[0018] Furthermore, the present invention provides a method for preparing the above-mentioned recombinant collagen filler material, characterized by comprising the following steps:

[0019] The carboxyl activator was dissolved in a buffer solution with a pH of 7.2-7.4 to obtain a carboxyl activator solution;

[0020] The recombinant collagen flocculant and recombinant collagen were added together to the carboxyl activator solution and stirred until homogeneous to obtain a mixed system. The mixed system was then allowed to stand to obtain a gel. The mass fraction of recombinant collagen in the mixed system was 1.0%~10.0%, and the mass fraction of recombinant collagen flocculant was 1.0%~50.0%.

[0021] The gel is dialyzed, then filled and sterilized to obtain recombinant collagen filler material.

[0022] The above method is characterized in that the carboxyl activator is selected from at least one of the following condensation systems: (1) carbodiimide condensing agents, or a combination of carbodiimide condensing agents with N-hydroxyimide stabilizers and / or N-hydroxytriazole stabilizers; (2) triazine condensing agents.

[0023] The method described above is characterized in that the buffer solution is any one of phosphate buffer solution, 4-hydroxyethylpiperazine ethanesulfonic acid (HEPES) buffer solution, 3-morpholinopropanesulfonic acid (MOPS) buffer solution, and piperazine-1,4-diethanesulfonic acid (PIPES) buffer solution.

[0024] The above method is characterized in that the stirring rate is 100r / min to 500r / min, the stirring time is 10min to 30min, and the standing time is 2h to 24h; the molar ratio of the side chain carboxyl groups of the recombinant collagen and the recombinant collagen flocculant to the carboxyl activator is (0.1 to 1):1.

[0025] Furthermore, the present invention provides an application of the above-mentioned recombinant collagen filler material in the preparation of soft tissue filler materials.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1. The recombinant collagen filler material of this invention is made by cross-linking recombinant collagen flocculants and recombinant collagen with a carboxyl activator. By controlling the compounding ratio of recombinant collagen flocculants and recombinant collagen, the prepared filler gel exhibits shear-thinning characteristics and excellent thixotropic recovery ability. Specifically, the thixotropic recovery rate of the filler material prepared by this invention is 92.9%~95.8%, indicating that the material can quickly recover its viscoelastic state after injection, which is beneficial for in-situ shaping at the filling site and reduces the risk of displacement. The shear-thinning factor is 53.89~149.71, indicating that the viscosity of the material is significantly reduced under high shear conditions, resulting in smooth injection and facilitating clinical injection operations, thus balancing clinical ease of operation with the stability of the filling effect.

[0028] 2. The recombinant collagen filler material prepared by this invention has a light transmittance of 5.7%~8.5% at a wavelength of 450nm. This effectively avoids the bluish tinge problem at the filling site caused by the Tyndall effect in traditional nanoscale transparent collagen gels, thus improving the naturalness and aesthetics of the filling effect.

[0029] 3. The mechanical properties and anti-degradation stability of the recombinant collagen filler material prepared by this invention are improved. Dynamic rheological testing showed that the storage modulus of the filler material was 320.52 Pa to 580.74 Pa. In vitro collagenase degradation experiments showed that the effective filling time of the example was more than 13 days. In vivo degradation experiments showed that the injection site still maintained a slight bulge 6 months after injection. Masson staining results showed that gel residue was visible in the injection site tissue, and the collagen fibers increased compared to the initial injection period.

[0030] 4. This invention prepares recombinant collagen flocculants using alcohol precipitation and gradient salting-out processes, with a specific surface area of ​​0.27~0.37 m². 2 / g, with a median particle size of 23μm~58μm; however, after changing the preparation process conditions, the specific surface area of ​​the resulting flocculants was only 0.04~0.19m². 2 / g. The filling material constructed by cross-linking the flocculants and recombinant collagen described in this invention exhibits superior storage modulus and effective filling time (accelerated in vitro test) compared to the control group, indicating that under the process conditions described in this invention, the specific surface area and particle size distribution of the flocculants are related to the mechanical properties and degradation resistance of the filling material.

[0031] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0032] Figure 1 The images show the morphology of the recombinant collagen filler materials prepared in Example 1 and Comparative Examples 1-3 of this invention immediately after subcutaneous injection in rats, and at 1 month, 3 months, and 6 months post-surgery.

[0033] Figure 2 Masson staining images of rat tissues after subcutaneous injection of the recombinant collagen filler materials prepared in Example 1 and Comparative Examples 1-3 of this invention for 6 months. Detailed Implementation

[0034] To make the above-mentioned objectives, features, and advantages of the present invention clearer and easier to understand, the specific embodiments of the present invention are described in detail below with reference to examples. The recombinant collagen used in the present invention is a commercially available product, including but not limited to recombinant type I collagen, recombinant type III collagen, recombinant type IV collagen, and recombinant type XVII collagen. The soft tissue filling range of the present invention includes, but is not limited to, areas requiring superficial filling such as tear troughs and nasolabial folds; areas requiring medium-depth filling such as temples, nose, and chin; and areas requiring supplementation such as nasolabial folds, corners of the mouth, and forehead / temporal region. Unless otherwise specified, the technical means used in the following embodiments are conventional means well known to those skilled in the art, and the materials and reagents used in the following embodiments are all commercially available unless otherwise specified. The following specific embodiments illustrate the content of the present invention, and the following description is not intended to limit the present invention.

[0035] This invention uses potentiometric titration to determine the molar amount of carboxyl groups in the side chains of recombinant collagen.

[0036] When a carbodiimide condensing agent is used in combination with an N-hydroxyimide stabilizer and / or an N-hydroxytriazole stabilizer, the preferred molar ratio of the carbodiimide condensing agent to the stabilizer (or, if multiple, the total molar amount) is 1:1. Those skilled in the art can make conventional adjustments to this ratio based on actual reaction conditions to obtain the desired crosslinking efficiency.

[0037] In this invention, the term "recombinant collagen flocculant" refers to a flocculant with a "microsphere-fiber" composite structure formed by the self-assembly of recombinant collagen molecules through alcohol precipitation and gradient salting out.

[0038] Example 1

[0039] The preparation method of the recombinant collagen filler material in this embodiment includes the following steps:

[0040] Step 1: Dissolve the carboxyl activator in a phosphate buffer solution with a pH of 7.2 to obtain a carboxyl activator solution; the carboxyl activator is DMTMM;

[0041] Step 2: Add the recombinant collagen flocculant and recombinant collagen together to the carboxyl activator solution mentioned in Step 1, stir at 340 r / min for 30 min to obtain a mixed system, and then let the mixed system stand for 16 h to obtain a gel;

[0042] Step 3: Dialyze the gel described in Step 2, then fill and sterilize it to obtain recombinant collagen filler material.

[0043] The molar ratio of the total side chain carboxyl groups of recombinant collagen flocculants and recombinant collagen to DMTMM is 0.8:1; in the mixed system, the mass fraction of recombinant collagen is 3.8%, and the mass fraction of recombinant collagen flocculants is 26.8%.

[0044] The preparation method of the recombinant collagen flocculant is as follows:

[0045] Step 201: Add recombinant collagen to a phosphate buffer solution with a pH of 7.2 to prepare a recombinant collagen solution with a mass fraction of 1.7%.

[0046] Step 202: While stirring at 180 r / min, add anhydrous ethanol dropwise to the recombinant collagen solution from step 201 at a rate of 0.3 mL / min until the volume ratio of anhydrous ethanol to recombinant collagen solution is 1:1.7. After the addition is complete, continue stirring at 180 r / min for 3.5 h to obtain product 1.

[0047] Step 203: Centrifuge product 1 obtained in step 202 at 4300 r / min for 10 min, discard the supernatant, wash, and dry to obtain product 2;

[0048] Step 204: Disperse product 2 obtained in step 203 in a pH 7.2 phosphate buffer solution containing 0.15 mol / L ammonium sulfate, controlling the mass fraction of product 2 to be 4.3%, and stir at 28 r / min for 3.1 h; then, adjust the concentration of ammonium sulfate in the system to 0.38 mol / L, and stir at 185 r / min for 4.2 h; finally, adjust the concentration of ammonium sulfate in the system to 0.77 mol / L, stir until the salt is completely dissolved, and let stand for 12 h to obtain product 3;

[0049] Step 205: Filter, wash and dry the product 3 obtained in step 204 to obtain recombinant collagen flocculent.

[0050] Example 2

[0051] The preparation method of the recombinant collagen filler material in this embodiment includes the following steps:

[0052] Step 1: Dissolve the carboxyl activator in a HEPES buffer solution with a pH of 7.2 to obtain a carboxyl activator solution; the carboxyl activator is EDC / NHS.

[0053] Step 2: Add the recombinant collagen flocculant and recombinant collagen together to the carboxyl activator solution mentioned in Step 1, stir at 100 r / min for 10 min to obtain a mixed system, and then let the mixed system stand for 2 h to obtain a gel;

[0054] Step 3: Dialyze the gel described in Step 2, then fill and sterilize it to obtain recombinant collagen filler material;

[0055] The molar ratio of EDC to NHS is 1:1, and the molar ratio of the total side chain carboxyl groups of recombinant collagen flocculants and recombinant collagen to EDC is 0.1:1; in the mixed system, the mass fraction of recombinant collagen is 1.0%, and the mass fraction of recombinant collagen flocculants is 1.0%.

[0056] The preparation method of the recombinant collagen flocculant is as follows:

[0057] Step 201: Add recombinant collagen to a phosphate buffer solution with a pH of 7.2 to prepare a recombinant collagen solution with a mass fraction of 0.5%.

[0058] Step 202: While stirring at 100 r / min, add anhydrous ethanol dropwise to the recombinant collagen solution from step 201 at a rate of 0.1 mL / min until the volume ratio of anhydrous ethanol to recombinant collagen solution is 1:3. After the addition is complete, continue stirring at 100 r / min for 1 h to obtain product 1.

[0059] Step 203: Centrifuge product 1 obtained in step 202 at 3000 r / min for 1 min, discard the supernatant, wash, and dry to obtain product 2;

[0060] Step 204: Disperse product 2 obtained in step 203 in a pH 7.2 phosphate buffer solution containing 0.05 mol / L sodium sulfate, controlling the mass fraction of product 2 to 3.0%, and stir at 10 r / min for 1 h; then, adjust the concentration of sodium sulfate in the system to 0.30 mol / L, and stir at 100 r / min for 1 h; finally, adjust the concentration of sodium sulfate in the system to 0.70 mol / L, stir until the salt is completely dissolved, and let stand for 8 h to obtain product 3;

[0061] Step 205: Filter, wash and dry the product 3 obtained in step 204 to obtain recombinant collagen flocculent.

[0062] Example 3

[0063] The preparation method of the recombinant collagen filler material in this embodiment includes the following steps:

[0064] Step 1: Dissolve the carboxyl activator in a MOPS buffer solution with a pH of 7.4 to obtain a carboxyl activator solution; the carboxyl activator is EDC·Mel.

[0065] Step 2: Add the recombinant collagen flocculant and recombinant collagen together to the carboxyl activator solution mentioned in Step 1, stir at 500 r / min for 30 min to obtain a mixed system, and then let the mixed system stand for 24 h to obtain a gel;

[0066] Step 3: Dialyze the gel described in Step 2, then fill and sterilize it to obtain recombinant collagen filler material;

[0067] The molar ratio of the total side chain carboxyl groups of recombinant collagen flocculants and recombinant collagen to EDC·Mel is 1:1; in the mixed system, the mass fraction of recombinant collagen is 10.0%, and the mass fraction of recombinant collagen flocculants is 50.0%.

[0068] The preparation method of the recombinant collagen flocculant is as follows:

[0069] Step 201: Add recombinant collagen to a MOPS buffer solution with a pH of 7.4 to prepare a recombinant collagen solution with a mass fraction of 3.0%.

[0070] Step 202: While stirring at 300 r / min, add anhydrous ethanol dropwise to the recombinant collagen solution from step 201 at a rate of 0.5 mL / min until the volume ratio of anhydrous ethanol to recombinant collagen solution is 1:1. After the addition is complete, continue stirring at 300 r / min for 5 h to obtain product 1.

[0071] Step 203: Centrifuge product 1 obtained in step 202 at 5000 r / min for 10 min, discard the supernatant, wash, and dry to obtain product 2;

[0072] Step 204: Disperse product 2 obtained in step 203 in a pH 7.4 phosphate buffer solution containing 0.2 mol / L sodium chloride, controlling the mass fraction of product 2 to be 5.0%, and stir at 50 r / min for 5 h; then, adjust the concentration of sodium chloride in the system to 0.50 mol / L, and stir at 200 r / min for 5 h; finally, adjust the concentration of sodium chloride in the system to 0.90 mol / L, stir until the salt is completely dissolved, and let stand for 12 h to obtain product 3;

[0073] Step 205: Filter, wash and dry the product 3 obtained in step 204 to obtain recombinant collagen flocculent.

[0074] Example 4

[0075] The preparation method of the recombinant collagen filler material in this embodiment includes the following steps:

[0076] Step 1: Dissolve the carboxyl activator in a PIPES buffer solution with a pH of 7.3 to obtain a carboxyl activator solution; the carboxyl activator is EDC / HOBt and DMTMM·BF4;

[0077] Step 2: Add the recombinant collagen flocculant and recombinant collagen together to the carboxyl activator solution mentioned in Step 1, stir at 200 r / min for 15 min to obtain a mixed system, and then let the mixed system stand for 10 h to obtain a gel;

[0078] Step 3: Dialyze the gel described in Step 2, then fill and sterilize it to obtain recombinant collagen filler material;

[0079] The molar ratio of EDC to HOBt is 1:1, and the molar ratio of the total side chain carboxyl groups of recombinant collagen flocculants and recombinant collagen to EDC and DMTMM·BF4 is 1:1:1; in the mixed system, the mass fraction of recombinant collagen is 5.0%, and the mass fraction of recombinant collagen flocculants is 15.0%.

[0080] The preparation method of the recombinant collagen flocculant is as follows:

[0081] Step 201: Add recombinant collagen to HEPES buffer solution with pH 7.3 to prepare a recombinant collagen solution with a mass fraction of 2.0%.

[0082] Step 202: Under stirring at 200 r / min, add anhydrous ethanol dropwise to the recombinant collagen solution from step 201 at a rate of 0.3 mL / min until the volume ratio of anhydrous ethanol to recombinant collagen solution is 1:2. After the addition is complete, continue stirring at 150 r / min for 2 h to obtain product 1.

[0083] Step 203: Centrifuge product 1 obtained in step 202 at 4000 r / min for 5 min, discard the supernatant, wash, and dry to obtain product 2;

[0084] Step 204: Disperse product 2 obtained in step 203 in a pH 7.3 phosphate buffer solution containing 0.1 mol / L ammonium sulfate and 0.05 mol / L sodium sulfate, controlling the mass fraction of product 2 to 4.0%, and stir at 30 r / min for 3 h; then, adjust the total concentration of ammonium sulfate and sodium sulfate in the system to 0.40 mol / L, and stir at 150 r / min for 2 h; finally, adjust the total concentration of ammonium sulfate and sodium sulfate in the system to 0.80 mol / L, stir until the salt is completely dissolved, and let stand for 10 h to obtain product 3;

[0085] Step 205: Filter, wash and dry the product 3 obtained in step 204 to obtain recombinant collagen flocculent.

[0086] Example 5

[0087] The preparation method of the recombinant collagen filler material in this embodiment includes the following steps:

[0088] Step 1: Dissolve the carboxyl activator in a phosphate buffer solution with a pH of 7.3 to obtain a carboxyl activator solution; the carboxyl activator is DMTMM·MeSO4;

[0089] Step 2: Add the recombinant collagen flocculant and recombinant collagen together to the carboxyl activator solution mentioned in Step 1, stir at 300 r / min for 20 min to obtain a mixed system, and then let the mixed system stand for 18 h to obtain a gel;

[0090] Step 3: Dialyze the gel described in Step 2, then fill and sterilize it to obtain recombinant collagen filler material.

[0091] The molar ratio of the total side chain carboxyl groups of recombinant collagen flocculants and recombinant collagen to DMTMM·MeSO4 is 0.7:1; in the mixed system, the mass fraction of recombinant collagen is 8.0%, and the mass fraction of recombinant collagen flocculants is 40.0%.

[0092] The preparation method of the recombinant collagen flocculant is as follows:

[0093] Step 201: Add recombinant collagen to a phosphate buffer solution with a pH of 7.2 to prepare a recombinant collagen solution with a mass fraction of 1.5%.

[0094] Step 202: Under stirring at 250 r / min, add anhydrous ethanol dropwise to the recombinant collagen solution from step 201 at a rate of 0.4 mL / min until the volume ratio of anhydrous ethanol to recombinant collagen solution is 2:3. After the addition is complete, continue stirring at 150 r / min for 2 h to obtain product 1.

[0095] Step 203: Centrifuge product 1 obtained in step 202 at 4500 r / min for 8 min, discard the supernatant, wash, and dry to obtain product 2;

[0096] Step 204: Disperse product 2 obtained in step 203 in a pH 7.4 phosphate buffer solution containing 0.1 mol / L ammonium sulfate and 0.05 mol / L disodium hydrogen phosphate, controlling the mass fraction of product 2 to be 4.0%, and stir at 35 r / min for 4 h; then, adjust the total concentration of ammonium sulfate and disodium hydrogen phosphate in the system to 0.45 mol / L, and stir at 150 r / min for 2 h; finally, adjust the concentration of ammonium sulfate and disodium hydrogen phosphate in the system to 0.85 mol / L, stir until the salt is completely dissolved, and let stand for 10 h to obtain product 3;

[0097] Step 205: Filter, wash and dry the product 3 obtained in step 204 to obtain recombinant collagen flocculent.

[0098] Comparative Example 1

[0099] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the recombinant collagen was first mixed with a carboxyl activator solution and then mixed with the recombinant collagen flocculent. Everything else was the same as in Example 1.

[0100] The specific preparation method of Comparative Example 1 is as follows:

[0101] Step 1: Dissolve the carboxyl activator in a phosphate buffer solution with a pH of 7.2 to obtain a carboxyl activator solution; the carboxyl activator is DMTMM;

[0102] Step 2: Add the recombinant collagen to the carboxyl activator solution mentioned in Step 1, stir at 340 r / min for 30 min to obtain mixed solution 1, and then let mixed solution 1 stand for 16 h to obtain gel;

[0103] Step 3: After dialysis treatment of the gel described in Step 2, mix it evenly with the recombinant collagen flocculant, then fill and sterilize it to obtain the recombinant collagen filler material.

[0104] The preparation process of the recombinant collagen flocculant in Comparative Example 1 was the same as that in Example 1.

[0105] Comparative Example 2

[0106] The difference between this comparative example and Example 1 is that Comparative Example 2 does not contain recombinant collagen flocculants; otherwise, it is the same as Example 1.

[0107] Comparative Example 3

[0108] The difference between this comparative example and Example 1 is that Comparative Example 3 uses a one-step salting-out method to prepare recombinant collagen flocculants, while all other aspects are the same as in Example 1.

[0109] The specific preparation method of the recombinant collagen flocculant described in Comparative Example 3 is as follows:

[0110] Step 201: Add recombinant collagen to a phosphate buffer solution with a pH of 7.2 to prepare a recombinant collagen solution with a mass fraction of 1.7%.

[0111] Step 202: Under stirring at 180 r / min, add anhydrous ethanol dropwise to the recombinant collagen solution from step 201 at a rate of 0.3 mL / min until the volume ratio of anhydrous ethanol to recombinant collagen solution is 1:1.7. After the addition is complete, continue stirring at the same stirring rate for 3.5 h to obtain product 1.

[0112] Step 203: Centrifuge product 1 obtained in step 202 at 4300 r / min for 10 min, discard the supernatant, wash, and dry to obtain product 2;

[0113] Step 204: Disperse the product 2 obtained in step 203 in a phosphate buffer solution with pH 7.2 containing 0.77 mol / L ammonium sulfate, control the mass fraction of product 2 to be 4.3%, stir at a rate of 28 r / min for 3.1 h, and let stand for 12 h to obtain product 3;

[0114] Step 205: Filter, wash and dry the product 3 obtained in step 204 to obtain recombinant collagen flocculent.

[0115] Comparative Example 4

[0116] The difference between this comparative example and Example 1 is that in Comparative Example 4, the mass fraction of recombinant collagen flocculants in the mixed system is 55.0%, while all other aspects are the same as in Example 1.

[0117] Comparative Example 5

[0118] The difference between this comparative example and Example 1 is that in Comparative Example 5, the mass fraction of the recombinant collagen solution in step 201 is 0.1%, while all other aspects are the same as in Example 1.

[0119] Comparative Example 6

[0120] The difference between this comparative example and Example 1 is that in Comparative Example 6, the mass fraction of the recombinant collagen solution in step 201 is 5.0%, while all other aspects are the same as in Example 1.

[0121] Comparative Example 7

[0122] The difference between this comparative example and Example 1 is that in Comparative Example 7, anhydrous ethanol was added dropwise to the recombinant collagen solution from Step 201 at a rate of 0.3 mL / min while stirring at 70 r / min in step 202. All other aspects were the same as in Example 1.

[0123] Comparative Example 8

[0124] The difference between this comparative example and Example 1 is that in Comparative Example 8, anhydrous ethanol was added dropwise at 0.3 mL / min to the recombinant collagen solution in Step 201 while stirring at 500 r / min in step 202. All other aspects were the same as in Example 1.

[0125] Comparative Example 9

[0126] The difference between this comparative example and Example 1 is that in Comparative Example 9, anhydrous ethanol is added dropwise to the recombinant collagen solution from Step 201 at a rate of 0.01 mL / min in step 202. All other aspects are the same as in Example 1.

[0127] Comparative Example 10

[0128] The difference between this comparative example and Example 1 is that in Comparative Example 10, anhydrous ethanol is added dropwise to the recombinant collagen solution in step 201 at a rate of 1 mL / min in step 202, while all other steps are the same as in Example 1.

[0129] Comparative Example 11

[0130] The difference between this comparative example and Example 1 is that, in Comparative Example 11, the product 2 obtained in step 203 was dispersed in a phosphate buffer solution containing 0.03 mol / L ammonium sulfate at pH 7.2, while all other aspects were the same as in Example 1.

[0131] Comparative Example 12

[0132] The difference between this comparative example and Example 1 is that, in Comparative Example 12, the product 2 obtained in step 203 was dispersed in a phosphate buffer solution containing 0.3 mol / L ammonium sulfate at pH 7.2, while all other aspects were the same as in Example 1.

[0133] Comparative Example 13

[0134] The difference between this comparative example and Example 1 is that, in Comparative Example 13, the product 2 obtained in step 203 was dispersed in a pH 7.2 phosphate buffer solution containing 0.15 mol / L ammonium sulfate, and the mass fraction of product 2 was controlled to be 4.3%, and the mixture was stirred at 28 r / min for 3.1 h; subsequently, the concentration of ammonium sulfate in the system was adjusted to 0.25 mol / L, and the mixture was stirred at 185 r / min for 4.2 h; all other aspects were the same as in Example 1.

[0135] Comparative Example 14

[0136] The difference between this comparative example and Example 1 is that, in Comparative Example 14, in step 204, the product 2 obtained in step 203 was dispersed in a pH 7.2 phosphate buffer solution containing 0.15 mol / L ammonium sulfate, and the mass fraction of product 2 was controlled to be 4.3%, and the mixture was stirred at 28 r / min for 3.1 h; subsequently, the concentration of ammonium sulfate in the system was adjusted to 0.65 mol / L, and the mixture was stirred at 185 r / min for 4.2 h; all other aspects were the same as in Example 1.

[0137] Comparative Example 15

[0138] The difference between this comparative example and Example 1 is that, in Comparative Example 15, in step 204, product 2 obtained in step 203 was dispersed in a pH 7.2 phosphate buffer solution containing 0.15 mol / L ammonium sulfate, and the mass fraction of product 2 was controlled to be 4.3%, and the mixture was stirred at 28 r / min for 3.1 h; subsequently, the concentration of ammonium sulfate in the system was adjusted to 0.38 mol / L, and the mixture was stirred at 185 r / min for 4.2 h; finally, the concentration of ammonium sulfate in the system was adjusted to 0.60 mol / L, and the mixture was stirred until the salt was completely dissolved, and then allowed to stand for 12 h to obtain product 3; all other aspects were the same as in Example 1.

[0139] Comparative Example 16

[0140] The difference between this comparative example and Example 1 is that, in Comparative Example 16, in step 204, product 2 obtained in step 203 was dispersed in a pH 7.2 phosphate buffer solution containing 0.15 mol / L ammonium sulfate, and the mass fraction of product 2 was controlled to be 4.3%, and the mixture was stirred at 28 r / min for 3.1 h; subsequently, the concentration of ammonium sulfate in the system was adjusted to 0.38 mol / L, and the mixture was stirred at 185 r / min for 4.2 h; finally, the concentration of ammonium sulfate in the system was adjusted to 1.00 mol / L, and the mixture was stirred until the salt was completely dissolved, and then allowed to stand for 12 h to obtain product 3; all other aspects were the same as in Example 1.

[0141] Performance testing

[0142] 1. Specific surface area determination

[0143] The specific surface area of ​​recombinant collagen flocculants was determined using the static volumetric method. This method follows GB / T19587-2017, "Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method". Specifically, the sample was subjected to a vacuum of 10 °C at 70 °C. -3 After degassing for 12 h under Pa conditions, using high-purity nitrogen as the adsorbate, adsorption isotherms were measured at liquid nitrogen temperature (77.4 K) within the relative pressure range of P / P0 = 0.05–0.35. The monolayer adsorption capacity was calculated using the BET equation. Each sample was measured in triplicate, and the average value was taken. Detailed data are shown in Table 1.

[0144] 2. Laser particle size analysis

[0145] A suitable amount of recombinant collagen flocculant was gently dispersed in purified water, and the particle size distribution was determined using a laser particle size analyzer. This determination method follows GB / T 19077-2024, "Particle Size Analysis - Laser Diffraction Method". The test conditions were: 5%–15% light blocking, measured under constant temperature conditions, with D... 50 The median particle size was used as the macroscopic size of the flocculants. The measurements were performed in three parallel trials, and the average value was taken.

[0146] Table 1. Summary of specific surface area and median particle size test results of recombinant collagen flocs prepared in Examples 1-5, Comparative Examples 3, and Comparative Examples 5-16.

[0147] experimental group <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Median particle size D 50 (μm)]]> Example 1 0.33 47±11 Example 2 0.27 58±9 Example 3 0.37 23±5 Example 4 0.31 40±12 Example 5 0.35 46±8 Comparative Example 3 0.04 45±10 Comparative Example 4 0.33 46±9 Comparative Example 5 0.18 42±10 Comparative Example 6 0.30 50±13 Comparative Example 7 0.27 52±12 Comparative Example 8 0.38 25±6 Comparative Example 9 0.36 43±9 Comparative Example 10 0.22 55±15 Comparative Example 11 0.05 48±11 Comparative Example 12 0.09 46±10 Comparative Example 13 0.11 44±9 Comparative Example 14 0.10 49±10 Comparative Example 15 0.13 45±9 Comparative Example 16 0.19 47±10

[0148] As can be seen from Table 1, D in Examples 1-5 50 Its diameter ranges from 23±5μm to 58±9μm, and its specific surface area ranges from 0.27 to 0.37m². 2 / g. Comparative Example 3 (0.04m 2 / g) and comparative examples 11~16 (0.05~0.19m) 2 The specific surface area of ​​the microspheres ( / g) was significantly lower than that of the examples, indicating that under the same alcohol precipitation conditions, changes in salting-out method and salt concentration have a significant impact on the specific surface area. The examples used gradient salting-out, which, by controlling the salt concentration stepwise, facilitates the formation of fibrous structures on the surface of the microspheres, thereby increasing the specific surface area and forming a composite aggregate with microspheres as the core and fibrous structures bonded to the surface.

[0149] The specific surface areas of Comparative Example 5 (collagen concentration too low) and Comparative Example 10 (ethanol added too quickly) decreased to 0.18 m². 2 / g and 0.22m 2 / g indicates that deviations in parameters during the alcohol precipitation stage can affect the formation of the microsphere core and the subsequent development of fibrous structures.

[0150] 3. Transmittance determination of recombinant collagen filler materials

[0151] Place the sample to be tested in a 1 cm quartz cuvette and measure the transmittance (T%) at a wavelength of 450 nm using a UV-Vis spectrophotometer. See Table 2 for the data.

[0152] 4. Rheological property testing of recombinant collagen filler materials

[0153] The test method followed YY / T 1435-2016, "Guideline for Characterization of Hydrogels in Tissue-Engineered Medical Devices". Anton Paar MCR 102e rotational rheology was used, equipped with a parallel plate rotor (20 mm diameter). The test gap was 1.00 mm, the test temperature was 25℃, and an oscillating frequency scanning mode was employed. The strain amplitude was set to 1%, and the frequency scanning range was 0.01~1Hz. The storage modulus and loss modulus at 0.1Hz were recorded. Each sample was measured in triplicate, and the average value was taken. Data are shown in Table 2.

[0154] 5. Determination of shear thinning properties of recombinant collagen filler

[0155] Anton Paar MCR 102e rotational rheometer, equipped with a 20mm diameter parallel plate rotor, was used. The test gap was set to 1.00mm, and the test temperature was 25℃. The three-stage shear rate method (referring to ASTM D2196) was employed for measurement: first at 0.1s... -1 The viscosity was maintained at a certain shear rate for 60 s, and the initial viscosity η0 was recorded. Then, it was maintained at a certain shear rate for 100 s. -1 The viscosity was maintained at a shear rate of 0.1 s for 60 s, and the high shear viscosity η1 was recorded. Finally, it was restored to 0.1 s. -1 The sample was held at a shear rate of 120 s, and the recovered viscosity η2 was recorded. Each sample was tested in triplicate. The thixotropic recovery rate and shear thinning factor were calculated, and the average value was taken. The data are shown in Table 2.

[0156]

[0157]

[0158] 6. In vitro enzymatic degradation experiment of recombinant collagen filler material

[0159] Take 0.5 g of the gel sample to be tested, add 2 mL of 1 U / mL collagenase solution (prepared in pH 7.4 PBS, containing 10 mmol / L CaCl2), and incubate at 37℃ with shaking at 100 r / min for degradation. Samples are taken at predetermined time points, and residual gel is separated by centrifugation. After washing, the gel is vacuum dried to constant weight, and the mass loss rate is calculated. The time when the mass loss rate reaches 50% is recorded as the effective filling time. Each sample is measured in triplicate, and the average value is taken. Data are shown in Table 2.

[0160] 7. In vivo degradation experiment of recombinant collagen filler material

[0161] In vivo degradation experiments were conducted using subcutaneous implantation. SPF-grade SD rats, half male and half female, were randomly divided into three groups: the example group, the comparative group, and the blank control group, with six rats in each group. Rats were fasted for 12 hours before the experiment, but water was allowed. Preoperative anesthesia was administered via intraperitoneal injection of acetaminophen. After anesthesia, the rats were fixed on a surgical board, and the surgical area (approximately 5cm × 8cm) was prepared in the midline of the back. The surgical area was disinfected, and three subcutaneous injection points were selected sequentially from top to bottom on both sides of the midline of the spine. Samples from the example, comparative, and blank control groups were injected at each point, with a dose of approximately 0.5mL per point. Photographs were taken at 1 month, 3 months, and 6 months postoperatively to observe and record the skin elevation at the injection sites. The results are shown in the table below. Figure 1 .

[0162] Six months post-surgery, rats were sacrificed, and skin tissue from the injection sites and surrounding areas was collected. After fixation, embedding, and sectioning, Masson's trichrome staining method was used to observe tissue morphology and collagen regeneration. Results are shown below. Figure 2 .

[0163] Table 2 Performance test results of recombinant collagen filler materials prepared in the examples and comparative examples

[0164] experimental group Light transmittance (T%) Energy storage modulus (Pa) Loss modulus (Pa) Shear thinning factor Thixotropic recovery rate (%) Fill in the effective time (days) Example 1 6.2±0.5 525.43±25.38 126.32±11.27 128.61 94.2 >14 Example 2 8.5±0.7 320.52±21.08 78.51±8.33 53.89 93.5 ~13 Example 3 5.7±0.4 495.37±27.11 138.45±12.61 149.71 95.8 >14 Example 4 6.9±0.6 483.55±26.18 118.63±10.72 111.45 93.7 ~13 Example 5 7.1±0.6 580.74±28.53 115.27±9.88 107.85 92.9 >14 Comparative Example 1 12.3±1.1 151.73±24.18 62.47±7.12 15.63 72.1 ~7 Comparative Example 2 89.6±3.2 45.23±5.88 28.65±4.31 3.45 61.3 ~2 Comparative Example 3 9.4±0.8 220.93±18.35 85.36±9.24 31.65 80.2 ~5 Comparative Example 4 4.8±0.4 604.85±36.21 145.82±13.77 39.34 85.6 >14 Comparative Example 5 10.1±0.9 94.22±15.41 41.35±5.86 9.82 68.7 ~3 Comparative Example 6 8.7±0.7 489.25±28.55 121.36±11.42 40.14 82.3 ~12 Comparative Example 7 9.2±0.8 463.29±14.46 114.72±10.15 39.28 83.1 >14 Comparative Example 8 7.9±0.6 297.62±20.34 89.53±8.76 40.60 79.5 ~5 Comparative Example 9 7.0±0.5 481.73±20.05 114.38±9.63 104.69 81.9 ~13 Comparative Example 10 8.3±0.7 386.27±31.06 97.64±10.25 83.83 84.2 ~9 Comparative Example 11 11.2±1.0 182.68±15.16 72.19±7.83 29.73 75.8 ~5 Comparative Example 12 7.3±0.6 452.37±28.54 108.43±10.07 93.88 82.7 ~11 Comparative Example 13 8.8±0.7 287.14±25.86 79.82±8.11 43.31 80.6 ~7 Comparative Example 14 7.6±0.6 463.95±30.04 112.67±10.59 89.02 83.3 ~10 Comparative Example 15 8.1±0.7 351.15±26.31 88.46±9.03 57.76 81.1 ~8 Comparative Example 16 6.5±0.5 504.11±25.36 122.84±11.36 119.86 92.1 ~12

[0165] Examples 1-5 constructed microsphere-fiber composite structures (specific surface area 0.27-0.37 m²) using an alcohol precipitation + gradient salting-out process. 2 / g,D 50 The thickness is 23~58 μm. Based on this structure, the prepared filling material can effectively avoid the blueing problem at the injection site caused by the Tyndall effect in terms of optics (transmittance 5.7%~8.5%); in terms of mechanics (storage modulus 320.52~581.74 Pa; loss modulus 78.51~138.45 Pa), it has good resistance to deformation and support performance; in terms of injection (shear thinning factor 53.89~149.71, thixotropic recovery rate 92.9%~95.8%), it is easy to inject and the viscosity recovers quickly after injection, which is beneficial to in-situ plasticity and reduces the risk of displacement; in terms of degradation, in vitro accelerated degradation experiments show that the filling effect lasts for more than 13 to 14 days. In vivo experiments further confirm that, in Example 1, the injection site still maintains a slight bulge 6 months after the operation, and obvious gel residue and newly formed collagen fibers can be observed in the subcutaneous tissue, proving that the material has good in vivo support, anti-degradation and collagen regeneration capabilities.

[0166] As shown in Table 2, Comparative Examples 1-4 failed to achieve a balance between mechanical support, injection smoothness, and degradation resistance, with overall performance significantly lower than the examples. Specifically: Comparative Example 1's non-in-situ crosslinking resulted in a comprehensive decline in all properties (mechanical properties, injection performance, and degradation resistance); Comparative Example 2, with no flocculants, achieved a light transmittance of 89.6%, a storage modulus of 45.23 Pa, and an effective filling time of 2 days; Comparative Example 3, with one-step salting out, resulted in a specific surface area of ​​only 0.04 m². 2 / g, effective filling time 5 days; the shear thinning factor of Comparative Example 4 was only 39.34, which was much lower than that of Examples 1-5, indicating that although adding too much flocculant can improve mechanical strength and anti-degradation ability, the smoothness of injection is seriously reduced, which does not meet the requirements of clinical application.

[0167] Due to deviations in the parameters during the alcohol precipitation stage, Comparative Examples 5-10 exhibited varying degrees of performance degradation in terms of mechanical support, injection smoothness, and anti-degradation ability. Table 1 shows that the specific surface area of ​​Comparative Example 5 (collagen concentration 0.10%) and Comparative Example 10 (ethanol drip rate 1 mL / min) decreased to 0.18 m² / g and 0.22 m² / g, respectively. 2 / g, significantly lower than Example 1 (0.33m 2The low collagen concentration or excessively rapid ethanol addition during the alcohol precipitation stage severely affects the formation of the microsphere core and the subsequent development of the fiber network. Table 2 further confirms this: the storage modulus and effective filling time of Comparative Example 5 decreased by 82% and 79% respectively compared to Example 1, and the dilution factor and recovery rate were also significantly lower, proving that insufficient collagen molecules prevent the product from providing effective mechanical support and anti-degradation properties. Comparative Example 10 showed a thixotropic recovery rate of 84.2% and an effective filling time of approximately 9 days, indicating that excessively rapid ethanol addition affected fiber structure development, thereby weakening the material's mechanical properties, injection smoothness, and anti-degradation ability.

[0168] Due to deviations in the process parameters during the alcohol precipitation stage, the specific surface area and particle size of the flocs prepared in Comparative Examples 6-7 and 9 were similar to those in Example 1, but the shear thinning factor and thixotropic recovery rate of the filler materials prepared in Comparative Example 8 were lower than those in Example 1. Although the specific surface area of ​​Comparative Example 8 was similar to that of Example 1, the particle size was significantly smaller than that of Example 1. The storage modulus, effective filling time, shear thinning factor, and thixotropic recovery rate of its filler material were all lower than those in Example 1, indicating that the excessively high stirring rate (500 r / min) damaged the structural integrity of the flocs, leading to a significant decrease in performance. The above results show that the process parameters during the alcohol precipitation stage have a significant impact on the structure of the flocs and the injection performance, mechanical properties, and anti-degradation properties of the final product.

[0169] Comparative Examples 11-16 showed variations in salt concentration at each stage of gradient salting-out, resulting in different specific surface areas (0.05-0.19 m²) of the prepared flocs. 2 The concentration of [g] was significantly lower than that of the example (0.27~0.37m). 2 / g). When the salt concentration is too low (Comparative Examples 11, 13, 15), the floc structure is loose, leading to a decrease in the storage modulus of the filler material by 33%–65% and a decrease in the effective filling time by 43%–64%. When the salt concentration is too high (Comparative Examples 12, 14, 16), the specific surface area of ​​the floc is significantly reduced, and the recovery performance and degradation resistance of the product are both decreased. The above results indicate that deviations in salt concentration during gradient salting-out have an adverse effect on the floc structure and the mechanical and degradation resistance properties of the filler material.

[0170] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the present invention. Any simple modifications, alterations, or equivalent structural changes made to the above embodiments based on the technical essence of the invention shall still fall within the protection scope of the present invention.

Claims

1. A recombinant collagen filler material, characterized in that, The recombinant collagen flocculant is prepared by cross-linking recombinant collagen with a carboxyl activator. The recombinant collagen flocculant is a flocculant with a microsphere-fiber composite structure prepared by alcohol precipitation and gradient salting out of a recombinant collagen solution.

2. The recombinant collagen filler material according to claim 1, characterized in that, The method for preparing the recombinant collagen flocculant includes: Step 1: Add recombinant collagen to a buffer solution with a pH of 7.2-7.4 to prepare a recombinant collagen solution with a mass fraction of 0.5%-3.0%; Step 2: Under stirring conditions, anhydrous ethanol is added dropwise to the recombinant collagen solution described in Step 1. After the addition is complete, stirring is continued to obtain product 1. Step 3: Centrifuge, wash, and dry the product 1 obtained in Step 2 to obtain product 2; Step 4: Perform gradient salting out on product 2 obtained in step 3. The specific process includes: dispersing product 2 at a mass fraction of 3.0% to 5.0% in a phosphate buffer solution with a total salt concentration of 0.05 mol / L to 0.20 mol / L and a pH of 7.2 to 7.4, and stirring at a rate of 10 r / min to 50 r / min for 1 h to 5 h; then increasing the total salt concentration in the system to 0.30 mol / L to 0.50 mol / L, and stirring at a rate of 100 r / min to 200 r / min for 1 h to 5 h; then increasing the total salt concentration in the system to 0.70 mol / L to 0.90 mol / L, stirring until the salt dissolves, and then allowing it to stand for 8 h to 12 h to obtain product 3. Step 5: Filter, wash and dry the product 3 obtained in step 4 to obtain recombinant collagen flocculent.

3. The recombinant collagen filler material according to claim 2, characterized in that, The buffer solution mentioned in step one is any one of phosphate buffer solution, 4-hydroxyethylpiperazine ethanesulfonic acid (HEPES) buffer solution, 3-morpholinopropanesulfonic acid (MOPS) buffer solution and piperazine-1,4-diethanesulfonic acid (PIPES) buffer solution; The salt used to increase the salt concentration in step four is one or more of the following: ammonium sulfate, sodium sulfate, disodium hydrogen phosphate, potassium dihydrogen phosphate, and sodium chloride.

4. The recombinant collagen filler material according to claim 2, characterized in that, In step two, the stirring rate is 100 r / min to 300 r / min, the volume ratio of anhydrous ethanol to recombinant collagen solution is 1: (1~3), the dropping rate of anhydrous ethanol is 0.1 mL / min to 0.5 mL / min, and after the dropping is completed, continue stirring at a rate of 100 r / min to 300 r / min for 1 h to 5 h.

5. The recombinant collagen filler material according to claim 2, characterized in that, The centrifugation rate in step three is 3000 r / min to 5000 r / min, and the centrifugation time is 1 min to 10 min.

6. A method for preparing the recombinant collagen filler material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: The carboxyl activator was dissolved in a buffer solution with a pH of 7.2-7.4 to obtain a carboxyl activator solution; The recombinant collagen flocculant and recombinant collagen were added together to the carboxyl activator solution and stirred until homogeneous to obtain a mixed system. The mixed system was then allowed to stand to obtain a gel. The mass fraction of recombinant collagen in the mixed system was 1.0%~10.0%, and the mass fraction of recombinant collagen flocculant was 1.0%~50.0%. The gel is dialyzed, then filled and sterilized to obtain recombinant collagen filler material.

7. The method according to claim 6, characterized in that, The carboxyl activator is selected from at least one of the following condensation systems: (1) carbodiimide condensing agents, or a combination of carbodiimide condensing agents with N-hydroxyimide stabilizers and / or N-hydroxytriazole stabilizers; (2) triazine condensing agents.

8. The method according to claim 6, characterized in that, The buffer solution is any one of phosphate buffer solution, 4-hydroxyethylpiperazine ethanesulfonic acid (HEPES) buffer solution, 3-morpholinopropanesulfonic acid (MOPS) buffer solution, and piperazine-1,4-diethanesulfonic acid (PIPES) buffer solution.

9. The method according to claim 6, characterized in that, The stirring rate is 100r / min to 500r / min, the stirring time is 10min to 30min, and the standing time is 2h to 24h; the molar ratio of the side chain carboxyl groups of the recombinant collagen and the recombinant collagen flocculant to the carboxyl activator is (0.1 to 1):

1.

10. The application of the recombinant collagen filler material as described in claim 1 in the preparation of soft tissue filler materials.

Citation Information

Patent Citations

  • Crosslinked recombinant collagen gel as well as preparation method and application thereof

    CN119101256A